Design of Photovoltaic as Energy Source at Government Office in Pangkalpinang - Ahmad Ferdiansyah; Ghiri Basuki Putra; Wahri Sunanda (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
In the regulation of the general energy plan for the Bangka Belitung region, it is targeted that the total use of new and renewable energy will reach 17.21% in 2025 and 30.97% in 2050. This, of course, requires a measurable implementation to achieve this. In this regard, a photovoltaic design was carried out as a source of electrical energy in one of the government offices in Pangkalpinang. This office's daily demand for electrical energy is 78.79 kWh, with an average solar irradiance of 487.51 W/m2 and a measured ambient temperature of 26o – 33.3o C. The modeling is carried out using three types of photovoltaic panels, a namely polycrystalline, monocrystalline and thin film with a supply power is combined with a source from PLN and 100% photovoltaic